2021
DOI: 10.3390/agronomy11112326
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen, Azoxystrobin and a Biostimulant Based on Brown Algae and Yeast on Wild Rocket Features at Harvest and During Storage

Abstract: Recently, the use of biostimulant substances of different origins has been affirmed. They act differently on the physiological processes of the plant, helping to improve its productive response and resistance to biotic and abiotic stress. Therefore, the response of the wild rocket to two substances known to have biostimulating activity (Azoxystrobin, and a fluid extract of brown algae and yeast), was evaluated. Two experimental trials (Exp 1 and Exp 2) were carried out in the greenhouse. The collected product,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…This could be due to an increase in the amino acid content in LDPH-treated plants, which can enhance photosynthetic pigment production [ 5 ]. Furthermore, an increase in photosynthetic pigments has been reported in wild rocket treated with several PBs [ 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…This could be due to an increase in the amino acid content in LDPH-treated plants, which can enhance photosynthetic pigment production [ 5 ]. Furthermore, an increase in photosynthetic pigments has been reported in wild rocket treated with several PBs [ 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…This response is due to response limits, being effective only within a specific range of concentrations [58]. At low doses, they may not be concentrated enough to trigger a response, while at high doses, they may exceed the optimal range, resulting in a lack of the desired effect [59]. In contrast, in S. rebaudiana and S. melongena, elevated concentrations showed increases in the RDW, STW, LDW, and TDW.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects of biostimulants on the growth and yield of rocket plants have been previously reported in the literature, which revealed that biostimulatory products of varied composition had a beneficial effect. For example, Candido et al [24] suggested that the use of an azoxystrobin-based biostimulant may increase the marketable yield of wild rocket plants (Diplotaxis tenuifolia L. DC) after the first crop cycle, while positive effects on yield were also recorded for biostimulants that contained protein hydrolysates obtained from legumes, tropical extracts, Trichoderma harzianum, Moringa oleifera extracts and Azoxystrobin [14,[39][40][41][42][43]. Additionally, Di Mola et al [38] suggested a significant increase in fresh yield in wild rocket plants treated with a biostimulant that contained seaweed and alfalfa extracts and amino acids, especially for harvests performed in late spring.…”
Section: Marketable Yield and Its Componentsmentioning
confidence: 99%
“…The positive effect of biostimulants on horticultural crops is due to the bioactive compounds present such as amino acids and phytohormones that stimulate plant growth by altering the primary metabolism, in addition to modulating the secondary metabolism of plants, through the improvement of nutrient uptake and triggering phytochemical synthesis [2,3,12]. Furthermore, biostimulants can increase pigment levels in leafy vegetables, as well as their antioxidant capacity [1], improve leaf color [13] and reduce nitrate content by boosting nitrogen metabolism [14]. Nitrate is mainly consumed through vegetables [15,16]; therefore, consumers are concerned about its concentration, notwithstanding the fact that these vegetables are endowed with functional qualities.…”
Section: Introductionmentioning
confidence: 99%